A Comprehensive Study on the Business Feasibility, and Optimization Model for Paddy Cultivation on Marginal Agricultural Land in Pekalongan District - Ramadhani, Farchan Mushaf Al; Ariadi, Heri; Mufid, Ahsarul; Handriatni, Ari; Sajuri, Sajuri; Ximenes, Romaldo da Costa (Jurnal AGRISEP, 2024)
Paddy cultivation on marginal land is the agribusiness activity. The aim of this research is to assess the feasibility status of paddy cultivation on marginal land and make efforts to optimize based on dynamic modeling system analysis. The research method used is descriptive quantitative with the dynamic modeling system analysis. The results show that the business profitability analysis shows a profit value of IDR 30,486,500, R/C Ratio 2.30, BEP unit 6,316 kg, BEP Sales IDR 15,477,220,-, and returnability 1.30%. This means this business is very profitable. The results of business financial analysis show an NPV IDR 2,536,754,052,-, profitability index 21.36%, IRR 14.21%, and payback period 14.4 years. This means this business is very worthy for development. The results of the dynamic modeling system analysis show that the paddy growth rate is influenced by using technology. Technology will influence rice growth of 3.5-7.0 cm. Nutrients influence the paddy biomass on marginal land. Using 10-20 kg/Ha of fertilizer will affect paddy biomass growth of 35-70 kg/Ha. The results of the dynamic model analysis show that the maximum paddy harvest production on marginal land is 25-50 kg/Ha/month with fertilizer use of 45-90 kg/Ha/month. This research concludes that the level of paddy cultivation feasibility on critical land is still quite feasible and profitable to develop. model analysis results show that of using agricultural technology and administering appropriate fertilizer doses will greatly determine the level of rice productivity on marginal agricultural land.